The condition and effects of evolutionary education in the parochial school - Schulteis, Michael (Curtin University, 2005)
The purpose of this research was to determine the condition of evolution education in American parochial schools and the effect of evolution education on students' attitudes toward science. Data were gathered using Eraser's Test of Science Related Attitudes (TOSRA) and Bilica's Teaching Evolutionary Topics Survey (TETS). The research participants consisted of 60.3% of biology teachers currently teaching in Lutheran high schools in the United States, and 479 Lutheran high school biology students grades 9-12 in California, Nevada, and Arizona. In the first attitudinal study done specifically on parochial students, statistical analysis confirmed the reliability and validity of the TOSRA instrument for parochial school students. In a quasi-experimental design, analysis revealed that student science attitudes do change as a result of participating in a unit on evolution in the first year biology classes of secondary parochial schools. The emphasis placed by teachers on particular evolutionary topics was also analysed. It was found that all Lutheran high school biology teachers present evolution to some extent although not all topics are emphasized equally. The results also demonstrate that parochial school teachers have nearly the same emphasis placed on evolution as do public school teachers.